Bringing Disciplines and People Together to Characterize the Plastic and Genetic Responses of Molluscs to Environmental Change. (26th August 2021) - Matoo, Omera B; Neiman, Maurine
Abstract: Molluscs are remarkably diverse and are found across nearly all ecosystems, meaning that members of this ancient animal phylum provide a powerful means to study genomic-phenotype connections in a climate change framework. Recent advances in genomic sequencing technologies and genome assembly approaches finally allow the relatively cheap and tractable assembly of high-quality mollusc genome resources. After a brief review of these issues and advances, we use a case-study approach to provide some concrete examples of phenotypic plasticity and genomic adaptation in molluscs in response to environmental factors expected to be influenced by climate change. Our goal is to use molluscs as a "common currency" to demonstrate how organismal and evolutionary biologists can use natural systems to make phenotype-genotype connections in the context of changing environments. In parallel, we emphasize the critical need to collaborate and integrate findings across taxa and disciplines in order to use new data and information to advance our understanding of mollusc biology in the context of global environmental change. We end with a brief synthetic summary of the papers inspired by the 2021 SICB Symposium "Genomic Perspectives in Comparative Physiology of Molluscs: Integration across Disciplines".